The influence of different parameters in tribological characteristics of pineapple/sisal/TiO2 filler incorporation. Issue 5 (June 2022) - Sumesh, KR; Saikrishnan, G; Pandiyan, P; Prabhu, L; Gokulkumar, S; Priya, AK; Spatenka, Petr; Krishna, Syam
In this experimentation hybrid composites using natural fibers and titanium oxide (TiO2 ) nano filler were fabricated using compression moulding technique. Pineapple (P) and Sisal (S) fibers were used as the natural reinforcements with epoxy as the matrix material. The mechanical results of flexural, impact and tensile properties found good improvement in the properties with SP fiber reinforcement (1:1 ratio) and TiO2 filler addition. The combination with 40 wt.% SP/5 wt.% TiO2 observed better mechanical results. The Taguchi optimization results showed lower Specific Wear Rate (SWR) by the incorporation of high TiO2 filler (5 wt.%) addition with the polymer-based composites. The filler substitutes replace the vacant space between fiber/matrix phase and add to the properties. The multi response optimization with TOPSIS proved that hybrid SP has the high influence in overall tribological properties of the natural fiber composites with rank 1 followed by filler incorporation. The results showed combination with 5 wt.% TiO2 /20 wt.% SP Hybrid fiber/500 m Sliding distance/Sliding speed of 1 m/s and applied load of 5 N having optimized results.